Voting, Inequality, and Redistribution - Rainald Borck (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
his paper surveys models of voting on redistribution. Under reasonable assumptions, the baseline model produces an equilibrium with the extent of redistributive taxation chosen by the median income earner; if the median is poorer than average, redistribution is from rich to poor. Increasing inequality increases redistribution. However, under dierent assumptions about the economic environment, redistribution may not be simply rich to poor, and inequality need not increase redistribution. Several lines of argument are presented, in particular, political participation, public provision of private goods, public pensions, and tax avoidance or evasion.
Keywords: O15; D72; 330; inequality; redistribution; voting; Einkommensumverteilung; Einkommensverteilung; Wahlverhalten; Wirtschaftsmodell